Adoption of ICT and its impact on cultural identity sustainability of ethnic minorities in Peninsular Malaysia - Choo, Yeong Khong (2015)
Information and Communication Technology (ICT) plays a crucial role in the present knowledge based globalization era and it has become a necessity for all members of the society in daily lives. In recent years, the increase in the adoption of ICT has significantly changed the manner in which society communicate and interact. The revolutions in the adoption of ICT have profound implications on social development and have pervaded every aspect of human life. An abundance of studies regarding the adoption of ICT have been carried out, but most of them tend to concern on mainstream society issues, specifically in the context of economic, organization and education, but only limited studies focuses on the impacts of ICT adoption towards the cultural identity. In light of this, the study aimed to identify the level of adoption of ICT and its impacts on cultural identity sustainability among the ethnic minorities in Peninsular Malaysia. This study employed a quantitative research approach. The study involved 400 respondents consisted of six different ethnic minority groups that aged 13 to 74 years old, recruited by using purposive sampling technique. An initial investigation done in the selected ethnic minorities settlements provided clearer understanding regarding the adoption of ICT in preserving their cultural identity. A self-developed instrument was used in order to achieve the research objectives in this study. The instrument used was translated to Malay language by using back to back translation and obtained high reliability. Correlation analysis and multiple regression analysis were used to elaborate the data of the study. After finding all the independent variables are correlated to the dependent variable, multiple regression analysis was conducted. The findings of the multiple regression indicated that three variables are significant in predicting the cultural identity sustainability which are relative advantage, resources and ICT use in preserving culture. The findings of the study also supported the Theory of Diffusion of Innovation which indicated that individuals‟ experience with one innovation influences the individual decision to adopt the innovation,whereby they adopted ICT if they perceived the ICT is useful to preserve their cultural identity. The findings also emphasized the importance of adoption of ICT in order to cope with the challenges brought by the stream of globalization and assist in planning and implementing ICT development among the ethnic minorities in Malaysia.